New moons - Verzutti, Erika 1971-; Cornell, Lauren 19XX- (Center for Curatorial Studies, Bard College, 2023)
"This volume takes an expansive view of the bold and influential practice of Brazilian artist Erika Verzutti (born 1971), surveying more than 60 pieces made over the past 15 years. In Verzutti's art, moons recur as symbols of renewal and the multiple phases that a person or entity can pass through. Her work presents novel modes of perception by orbiting outside set systems of being--zooming out, in a telescopic sense, to the point where the relations we take so seriously here on Earth can be rethought. Vibrant illustrations of individual works and installation views of New Moons, the artist's first US museum survey, highlight how her approaches to display and presentation reveal such relationships. Presenting original scholarship on the art historical and theoretical aspects of Verzutti's practice as well as the artist's own writing, this book offers insights on the inspiration and multifaceted ideas at play across her work."--
This book was published on the occasion of the exhibition Erika Verzutti: New Moons, on view at CCS Bard, June 24-October 15, 2023, curated by Lauren Cornell
Keywords: Verzutti, Erika -- 1971-; Verzutti, Erika / Exhibitions; Bildband; Ausstellungskatalog -- Center for Curatorial Studies -- 24.06.2023-15.10.2023 -- Annandale-on-Hudson, New York